Thermophysical performances of high-entropy (La0.2Nd0.2Yb0.2Y0.2Sm0.2)2Ce2O7 and (La0.2Nd0.2Yb0.2Y0.2Lu0.2)2Ce2O7 oxides. Issue 4 (15th February 2022) - Tang, An; Li, Bin; Sang, Weiwei; Hongsong, Zhang; Chen, Xiaoge; Zhang, Haoming; Ren, Bo
Abstract: Two High-entropy ceramics, (La0.2 Nd0.2 Yb0.2 Y0.2 Sm0.2 )2 Ce2 O7 (LNYSC) and (La0.2 Nd0.2 Yb0.2 Y0.2 Lu0.2 )2 Ce2 O7 (LNYLC) were synthesized using a sol-gel technique and sintering at high temperatures. The lattice type, micro-morphology, and thermophysical and mechanical properties of these oxides were investigated. The results showed that the obtained high-entropy powders and bulk samples have single fluorite lattice, dense microstructure, and clear grain boundary. These oxides have less thermal conductivities than (7YSZ), and the thermal conductivity of LNYLC is lower than that of LNYSC. The thermal expansion coefficients of these high-entropy oxides are larger than that of 7YSZ. Owing to the relative less negative electrical difference in LNYLC that in LNYSC, the thermal expansion coefficient of LNYLC is larger than that of LNYSC. Further, these oxides exhibit outstanding lattice stability up to 1200 °C, which can help to improve the durability of thermal barrier coatings. However, these oxides have lower mechanical properties compared to 7YSZ.